Platooning in UAM airspace structures: applying trajectory shaping guidance law and exploiting cooperative localization - Mayle, Melody N.; Sharma, Rajnikant (Frontiers in Aerospace Engineering, 2023)
A novel control technique for the platooning of aerial vehicles is introduced herein and its stability is analyzed. The controller applies a missile guidance law that was initially adapted for path following and subsequently extended to platooning. The positions of all the agents within a platoon employing this controller are estimated by exploiting cooperative localization and these estimated positions are fed back into the controller. Using simulation, the agents within a platoon are demonstrated to follow their desired path and avoid collision, in even in environments with intermittent GPS signals and limited sensing ranges.